Analysis Of Experiental Marketing, Service Quality, And Customer Satisfaction Towards Customer Loyalty At Hotel Grand Kanaya Medan - Heru Syahputra; Megasari Gusandra Saragih; Husni Muharram Ritonga (Journal of Management, Economic, and Accounting, 2026)
The purpose of this study is to analyze the influence of Experiential Marketing, Service Quality, and Customer Satisfaction on Customer Loyalty at the Grand Kanaya Hotel, Medan. The author conducted a preliminary survey in order to obtain information regarding the problem being studied, namely related to customer loyalty. The research approach used in this study is quantitative. Quantitative data is the analysis of data on numbers containing certain numerics. The population of this study is all Grand Kanaya Medan customers, and the sample was obtained through the results of sample calculations and obtained 99 respondents. Data collection techniques in this study are as follows: 1) questionnaires, 2) interviews, 3) observations. Data analysis techniques use 3 tests, namely: Data quality test, Classical Assumption Test, and Multiple Linear Regression Test. The results of this study indicate that experiential marketing variables have a positive and significant partial influence on Grand Kanaya Medan customer loyalty; service quality has a positive and significant partial influence on Grand Kanaya Medan customer loyalty; customer satisfaction has a positive and significant partial influence on Grand Kanaya Medan customer loyalty; and Experiential marketing, service quality, and customer satisfaction have a significant influence simultaneously on customer loyalty at Grand Kanaya Hotel Medan.